Asphalt concrete production process using waste mineral aggregate to replace machine-made sand
By screening, high-temperature calcining, acidification treatment and nanocatalyst loading, combined with the use of surfactants and functional enhancement materials, the problem of poor interfacial bonding performance of waste minerals in asphalt concrete is solved, and the production of high-performance asphalt mixtures is achieved, meeting the requirements of engineering performance and economic and environmental protection.
Patent Information
- Application Number
- CN202411935131.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
When the prior art uses waste mineral materials to replace machine sand, the lack of systematic surface treatment and modification processes, resulting in poor interface bonding performance and difficult to meet the mechanical properties and durability requirements of asphalt concrete.
By screening, high-temperature calcining, surface acidification treatment and nanocatalyst loading, the surfactant and chemical bonding performance are improved, and surfactant and functional enhancement materials are introduced into the mixture to optimize the ratio and construction process of the asphalt mixture.
It significantly improves the interface combination performance between waste minerals and asphalt, improves the uniformity, fatigue resistance and durability of asphalt mixture, meets the engineering performance requirements of asphalt concrete, and reduces raw material costs and reduces environmental impact.
Smart Images

Figure CN119874241A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building material production, and in particular to an asphalt concrete production process using waste mineral materials instead of machine-made sand. Background Art
[0002] With the acceleration of urbanization, the demand for high-quality building materials in road construction and construction projects continues to grow. As the main source of fine aggregate, artificial sand is widely used in asphalt concrete and concrete projects. Artificial sand is usually prepared by crushing and screening hard rocks such as limestone. Because of its good particle shape, particle size distribution and physical properties, it has long been favored in the engineering field. However, with the increasing scarcity of natural limestone resources, its mining and processing costs continue to rise, which not only greatly increases the cost of projects, but also further aggravates the over-dependence on natural resources and the damage to the ecological environment. Therefore, how to find an economically feasible and environmentally friendly alternative to artificial sand has become an important issue that the industry needs to solve urgently.
[0003] At the same time, a large amount of waste minerals (such as waste rocks) generated during mining and urban construction have not been fully utilized. Long-term accumulation not only occupies a large amount of land resources, but may also cause serious environmental pollution, including heavy metal infiltration and dust pollution in water and soil. Waste minerals are considered as potential substitutes for machine-made sand because of their abundant reserves and low cost. Since the surface of waste minerals is often covered with impurities, inactive oxides and organic pollutants, their interface bonding performance with bonding materials (such as asphalt or cement) is poor. At the same time, there may be water-absorbing pores or loose structures inside the minerals, which makes it difficult for the mechanical properties and durability to meet the actual needs when they are directly used in engineering materials. The utilization of waste minerals in the existing technology mainly focuses on simple cleaning or crushing, and fails to fundamentally solve the problems of insufficient chemical activity and weak cross-sectional bonding.
[0004] Therefore, the existing technology has many shortcomings in treating waste minerals to replace machine-made sand. First, the lack of systematic surface treatment and modification processes makes it difficult to effectively remove impurities and inactive layers on the surface of the minerals, resulting in the inability to significantly improve the interface bonding performance; secondly, deep processing technologies for waste minerals (such as high-temperature calcination, nano-modification, etc.) are rarely used, and their potential active sites have not been fully utilized, limiting the value of their resource utilization. Existing technologies focus more on the production and optimization of machine-made sand, but fail to organically combine the treatment of mine waste with the development of machine-made sand alternatives. Efficient resource utilization technology for waste minerals needs to be developed urgently to reduce the production cost of engineering materials, while solving the environmental protection problem of mine waste accumulation and promoting the sustainable development of the green building materials industry. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides an asphalt concrete production process using waste minerals instead of machine-made sand, which solves the problem that the prior art focuses more on the production and optimization of machine-made sand, but fails to organically combine the treatment of mining waste and the development of machine-made sand alternative materials.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: an asphalt concrete production process using waste mineral materials instead of machine-made sand, comprising the following steps: Screening the waste minerals to obtain fine aggregates with a particle size of 0.075 mm to 2.36 mm; The screened waste ore is calcined at high temperature; Carry out surface acidification treatment on waste ore after high-temperature calcination; Loading nanocatalysts on waste mineral materials that have undergone surface acidification treatment; Introducing surfactants on the surface of waste mineral materials; Mixing waste minerals, coarse aggregates, asphalt and functional enhancement materials in proportion to prepare an asphalt mixture, wherein the mass percentage of the waste minerals is 50% to 70%, the mass percentage of the coarse aggregates is 20% to 30%, the mass percentage of the asphalt is 5% to 8%, and the mass percentage of the functional enhancement materials is 0.5% to 1.5%; The prepared asphalt mixture is used for road construction.
[0007] Furthermore, the main purpose of screening is to remove large particles and fine powder impurities, ensure that the particle size of the waste mineral is uniform and meets the requirements of fine aggregate, avoid the influence of too large or too small particles on the fluidity and skeleton stability of the mixture, and provide a suitable particle surface area for subsequent steps.
[0008] High-temperature calcination decomposes organic matter on the surface of the ore and absorbs moisture, exposing the active sites of the ore and enhancing its surface chemical reactivity. In addition, the calcination process can also increase the hardness and wear resistance of the waste ore, providing the aggregate with stronger bearing capacity and stability.
[0009] The acidification treatment further removes oxides and calcifications on the surface of the mineral material through chemical corrosion, and at the same time forms an active film layer on the surface, which enhances the specific surface area and polarity of the mineral material surface, providing a good substrate for the subsequent attachment of nanocatalysts.
[0010] The loading of nanocatalysts further enhances the chemical reactivity and interfacial energy of the surface of waste minerals by depositing catalytically active substances (such as nano-TiO2 or CeO2) on the surface of minerals, making it easier for them to chemically combine with asphalt molecules and improve the overall bonding performance.
[0011] Surfactants enhance the wettability and dispersibility between waste minerals and asphalt by adjusting the surface electrical properties and hydrophilicity / hydrophobicity of particles, preventing minerals from agglomerating in the mixture, thereby improving the overall uniformity and stability.
[0012] Waste mineral materials, as fine aggregates, together with coarse aggregates, constitute the skeleton structure of the mixture. The coarse aggregates provide bearing and deformation resistance, and the waste mineral materials fill the gaps in the skeleton to ensure the compactness of the mixture. Asphalt, as a binder, provides flexibility and adhesion to the mixture, and functional enhancement materials (such as nanocatalysts or modified polymers) further optimize the bonding performance between mineral materials and asphalt.
[0013] By using the mixture in road construction, the performance of the waste mineral materials can be fully utilized, while ensuring that the road strength, durability and fatigue resistance meet the engineering requirements.
[0014] Preferably, the high-temperature calcination temperature of the waste ore is 600° C. to 800° C., the calcination time is 1.5 hours to 2 hours, and the equipment for high-temperature calcination is a rotary kiln.
[0015] Furthermore, the calcination temperature in the range of 600℃ to 800℃ can ensure that the organic matter and moisture on the surface of the ore are fully removed, while avoiding excessively high temperatures that may cause the surface of the ore to melt or deteriorate in performance; the calcination time is 1.5 hours to 2 hours, which can ensure that the active sites inside the particles are fully exposed. As a calcination equipment, the rotary kiln has the characteristics of uniform temperature distribution and high heat exchange efficiency, which can effectively improve the calcination quality.
[0016] Preferably, the surface acidification treatment comprises the following steps: Prepare a mixed acid solution, wherein the mixed acid solution is a mixture of 5% to 10% phosphoric acid and dilute hydrochloric acid in a ratio of 1:1, and adjust the pH value to 4.5 to 6; Soaking the calcined waste ore in the mixed acid solution for 30 to 60 minutes; The soaked waste minerals are rinsed with deionized water and dried.
[0017] Furthermore, the mixed acid solution chemically corrodes the surface of the mineral material in an acidic environment to remove impurities, improve the surface activity of the mineral material, and form a suitable acid film layer to provide a surface modification basis for subsequent steps. The immersion time is controlled within 30 minutes to 60 minutes to ensure that the acid solution fully reacts with the particle surface and avoids excessive corrosion of the particle surface due to too long a time. Flushing can effectively remove residual acid and avoid acid-base neutralization reactions in subsequent processes; drying can further reduce the surface moisture content of the mineral material and improve its stability.
[0018] Preferably, the nanocatalyst is nano-titanium dioxide or nano-cerium oxide with a particle size of 10nm to 50nm, and the mass concentration of the nanocatalyst solution is 0.5% to 1.5%.
[0019] Furthermore, nanoparticles with a particle size of 10nm to 50nm have a higher specific surface area and active sites, which are conducive to the uniform distribution of the catalyst on the surface of the mineral material. The solution mass concentration of 0.5% to 1.5% can ensure a moderate concentration of the catalyst to avoid agglomeration caused by too high concentration or the effect affected by too low concentration.
[0020] Preferably, the nanocatalyst loading comprises the following steps: Placing the waste mineral material in a vacuum coating device and uniformly spraying the nano catalyst solution; Dry the sprayed waste mineral material at a temperature of 100°C to 120°C for 1 to 2 hours; The dried waste ore is subjected to secondary calcination, the calcination temperature is 400° C. to 600° C., and the calcination time is 0.5 hour to 1 hour.
[0021] Furthermore, vacuum coating equipment can enhance the adhesion of the catalyst to the surface of the mineral material and ensure coating uniformity. Low-temperature drying can prevent catalyst deactivation and promote uniform fixation of the catalyst on the surface of the mineral material. Secondary calcination helps to enhance the bonding strength between the catalyst and the surface of the mineral material and activate the chemical properties of the catalyst.
[0022] Preferably, the surfactant is nonylphenol polyoxyethylene ether or sulfonate, and the mass concentration of the surfactant solution is 0.1% to 0.5%.
[0023] Furthermore, the surfactant improves the wettability and dispersibility of the mineral material and asphalt by adjusting the hydrophilicity and hydrophobicity of the mineral material surface, thereby promoting the uniform combination of the two. The mass concentration of the surfactant solution is 0.1% to 0.5%, which can ensure that the surfactant molecules are uniformly adsorbed on the mineral material surface, while avoiding the degradation of the mixture performance caused by excessive addition.
[0024] Preferably, the surfactant is introduced onto the surface of the waste mineral material by spraying, and is dried after being stirred evenly at room temperature.
[0025] Furthermore, the introduction of surfactants by spraying can ensure uniform distribution of the surfactant and avoid unevenness caused by local excess; stirring at room temperature helps the rapid adsorption of the surfactant, and the drying step can remove excess moisture on the surface, ensuring that the mineral material has good dispersibility and interface properties in subsequent preparation.
[0026] Preferably, the function-enhancing material is cement, lime powder or modified epoxy resin, wherein the addition amount of cement or lime powder is 2% to 3%, and the addition amount of modified epoxy resin is 0.5% to 1%.
[0027] Furthermore, functional reinforcing materials improve the tensile strength and fatigue resistance of asphalt mixtures by filling micropores in the mixture and enhancing the bonding strength between particles; cement and lime powder are alkaline active and can react chemically with silicates in mineral materials to increase interfacial strength; modified epoxy resins can further enhance the overall stability and durability of the mixture by forming a cross-linked network.
[0028] Preferably, the stirring temperature of the asphalt mixture is 160° C. to 180° C., and the stirring time is 90 seconds to 120 seconds.
[0029] Furthermore, a stirring temperature of 160°C to 180°C can make the asphalt reach the best fluidity state, ensuring that it can be evenly covered on the surface of mineral materials and aggregates; the stirring time is controlled at 90 seconds to 120 seconds to avoid asphalt aging due to too long a time, while ensuring sufficient mixing between the components, thereby improving the uniformity and stability of the mixture.
[0030] Preferably, when the asphalt mixture is used for road construction, the paving thickness is 5 cm to 15 cm, the initial compaction temperature is 90° C. to 110° C., and a steel wheel roller is used for compaction 3 to 5 times.
[0031] Furthermore, a paving thickness of 5cm to 15cm can ensure the flatness and bearing capacity of the road surface; initial compaction temperature controlled at 90℃ to 110℃ can enable the mixture to reach the best compaction state and prevent insufficient density due to low temperature; using a steel wheel roller to compact 3 to 5 times can effectively improve the density and shear strength of the mixture, ensuring that the road surface meets the use requirements.
[0032] The present invention provides an asphalt concrete production process using waste mineral materials to replace machine-made sand. It has the following beneficial effects: 1. The present invention adopts the technical scheme of screening, high-temperature calcination, acidification treatment and nanocatalyst loading of waste mineral materials, and significantly improves the surface activity and chemical bonding performance of waste mineral materials through deep modification, achieving the technical effect of effectively replacing traditional machine-made sand for asphalt concrete. Compared with the existing technology of directly using waste mineral materials as fine aggregates, which has the problems of insufficient surface activity and poor bonding performance, the present invention solves the shortcomings of low resource utilization rate of waste mineral materials and road performance that cannot meet engineering requirements.
[0033] 2. The present invention adopts the technical solution of introducing surfactants on the surface of waste mineral materials and loading functional reinforcement materials to improve the wettability and bonding performance between waste mineral materials and asphalt, and achieves the technical effect of significantly improving the uniformity and fatigue resistance of asphalt mixture. Compared with the prior art that does not fully regulate the interface between aggregates and asphalt, resulting in insufficient shear strength and durability of the pavement, the problem of pavement cracking and early damage caused by weak interface bonding performance is solved.
[0034] 3. The present invention adopts the technical solution of replacing machine-made sand with waste mineral materials, and achieves the technical effect of reducing the cost of raw materials and reducing the impact of mining on the environment by optimizing the treatment process and proportion design of waste mineral materials. Compared with the resource consumption and high cost problems caused by relying on natural machine-made sand as fine aggregate in the prior art, it solves the problems of tight supply of machine-made sand and high environmental pressure.
[0035] 4. The present invention adopts the technical scheme of optimizing the mixing process parameters of asphalt mixture, controlling the paving thickness and designing the compaction process, which ensures the uniformity and density of the asphalt mixture during the construction process, and achieves the technical effect of improving the bearing capacity of the pavement and extending the service life. Compared with the problem of poor pavement durability due to insufficient control of the mixture ratio and construction parameters in the prior art, the problem of the pavement being prone to settlement, cracks and other diseases is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Please see attached Figure 1 : Example 1: Using waste minerals instead of machine-made sand to prepare asphalt mixture for ordinary highway construction Description of Embodiments Screening and cleaning of waste minerals The waste mineral materials with a particle size of 0.075mm to 2.36mm are screened, washed, dried and set aside.
[0039] High temperature calcination Calcinate in a rotary kiln at 700°C for 1.8 hours to remove moisture and organic matter adsorbed on the surface of the ore.
[0040] Surface acidification Prepare a mixed solution of 6% phosphoric acid and 6% dilute hydrochloric acid (1:1 ratio), adjust the pH value to 5.0, soak the ore for 40 minutes, then rinse and dry.
[0041] Nanocatalyst loading A 1.0% concentration of nano titanium dioxide solution (particle size 20 nm) was evenly sprayed, and after drying at 110° C. for 1.5 hours, a secondary calcination at 500° C. for 0.8 hour was performed.
[0042] Surfactant treatment Spray 0.3% concentration of nonylphenol polyoxyethylene ether solution, stir evenly and then dry.
[0043] Asphalt mixture preparation and construction ratio: waste mineral material 60%, coarse aggregate (granite) 25%, asphalt 7%, functional enhancement material (lime powder) 3%.
[0044] Stir at 170℃ for 100 seconds, spread thickness is 10cm, initial pressing temperature is 100℃, and compact 4 times.
[0045] Comparative Example 1-1 (without surface acidification treatment) The process of this comparative example is completely consistent with that of Example 1, except for the surface acidification treatment step. The waste ore after high-temperature calcination is directly used for subsequent catalyst loading and mixed material preparation.
[0046] Comparative Example 1-2 (without using nano catalyst) The process of this comparative example is basically the same as that of Example 1, but the nano-catalyst loading step is omitted. The calcined ore material is directly sprayed with a surfactant after being acidified.
[0047] Comparative Examples 1-3 (Low-temperature calcination process) The calcination temperature in this comparative example was changed to 500° C., and the calcination time was shortened to 1 hour. The remaining steps were consistent with those in Example 1.
[0048] Summary of Examples In Example 1, the activity of the waste mineral material and the interface bonding performance with asphalt were significantly improved through a series of optimization steps such as screening, calcination, acidification, nanocatalyst loading and surfactant treatment. Compared with the comparative example, surface acidification, catalyst loading and high-temperature calcination played a key role in improving the overall performance of asphalt mixture, especially in ordinary roads, the balance between performance and cost was effectively achieved.
[0049] Example 2: High-performance waste mineral asphalt mixture for highway pavement Description of Embodiments Screening and high temperature calcination of waste ore The ore with a particle size of 0.075 mm to 1.25 mm was screened, and after cleaning, it was calcined at 750°C for 2 hours.
[0050] Surface acidification Prepare a mixed solution of 8% phosphoric acid and 8% dilute hydrochloric acid (1:1 ratio), adjust the pH value to 4.8, soak the mineral material for 50 minutes, then rinse and dry.
[0051] Nanocatalyst loading A 1.2% concentration of nano-cerium oxide solution (particle size 15 nm) was uniformly sprayed, and after drying at 115° C. for 1 hour, a secondary calcination at 450° C. for 0.5 hour was performed.
[0052] Functional enhancement material addition Add 0.8% modified epoxy resin emulsion.
[0053] Asphalt mixture preparation and construction ratio: waste mineral material 55%, coarse aggregate (limestone) 30%, asphalt 7%, functional enhancement material 0.8%.
[0054] Stir at 175℃ for 110 seconds, spread to a thickness of 8 cm, initial pressing temperature of 105℃, and compact 5 times.
[0055] Comparative Example 2-1 (no secondary calcination) This comparative example is basically the same as Example 2, but the secondary calcination step after the nanocatalyst is loaded is omitted, and the mineral material after the catalyst is sprayed is directly used for the preparation of asphalt mixture.
[0056] Comparative Example 2-2 (no functional enhancement material added) In this comparative example, no functional enhancement material (modified epoxy resin emulsion) was added in the process, and the remaining steps were the same as those in Example 2.
[0057] Comparative Example 2-3 (Insufficient Acidification Time) In this comparative example, during the acidification treatment stage, the immersion time of the ore was shortened to 20 minutes, and the other steps remained the same.
[0058] Summary of Examples In Example 2, in response to the requirements of highways for high strength, durability and fatigue resistance, strict acid treatment, nano-cerium oxide loading and modified epoxy resin reinforcement were used to ensure the high performance of the mixture. Comparative experiments show that secondary calcination and functional enhancement materials play a key role in improving performance, while shortening the acid treatment time may lead to a decrease in interface bonding ability.
[0059] Example 3: Economical waste mineral asphalt mixture for municipal road repair Description of Embodiments Screening and cleaning of waste minerals Screen the mineral materials with particle size of 0.15mm to 2.36mm, wash them and dry them for later use.
[0060] High temperature calcination The activity of the particles was partially improved after calcination at 650 °C for 1.5 h.
[0061] Acidification Prepare a mixed solution of 5% phosphoric acid and 5% dilute hydrochloric acid (1:1 ratio), adjust the pH value to 5.5, soak the mineral material for 30 minutes, then rinse and dry.
[0062] Nanocatalyst loading A nano titanium dioxide solution with a concentration of 0.8% was evenly sprayed, and dried at 100° C. for 1 hour, and the secondary calcination step was omitted.
[0063] Asphalt mixture preparation and construction ratio: waste mineral material 65%, coarse aggregate (limestone) 20%, asphalt 6%, functional enhancement material (cement) 2%.
[0064] Stir at 165℃ for 90 seconds, spread to a thickness of 6 cm, initial pressing temperature of 95℃, and compact 3 times.
[0065] Comparative Example 3-1 (catalyst loading omitted) The process of this comparative example is basically the same as that of Example 3, but the nanocatalyst loading step is omitted.
[0066] Comparative Example 3-2 (calcination temperature is insufficient) In this comparative example, the calcination temperature was adjusted to 500° C. and the calcination time was 1 hour, and the remaining steps were the same.
[0067] Summary of Examples Example 3 takes economy as the core, and aims at the performance requirements of municipal road repair, improves the resource utilization rate of waste mineral materials by simplifying process design and moderate optimization, and controls production costs at the same time. The comparative experimental results show that catalyst loading and reasonable calcination temperature play an important role in improving performance, while low calcination temperature and no catalyst loading will significantly affect the durability and uniformity of the road surface.
[0068] Example 4: Production process of waste mineral asphalt concrete based on nanomaterial optimization Specific steps Collection and preliminary treatment of waste minerals Collect waste material from mining operations or mine waste and send it to a processing station.
[0069] Use a vibrating screening machine to screen the waste minerals, remove lumps and impurities with a particle size greater than 2.36 mm, and retain fine aggregates with a particle size of 0.075 mm to 2.36 mm.
[0070] Composition analysis of waste minerals The chemical composition of the screened ore was tested using an X-ray fluorescence spectrometer (XRF) to analyze the contents of main components such as silicon, calcium, and iron.
[0071] If site conditions are limited, wet leaching can be used to make a preliminary judgment on the main components of the ore to ensure that the ore composition is appropriate.
[0072] Mixture design and auxiliary material adjustment According to the results of mineral composition analysis, adjust the addition ratio of cement or lime powder so that it accounts for 2% to 3% of the total mass of the mixture.
[0073] Nanomaterials are introduced as reinforcing agents (such as nano-silicon dioxide, with a particle size of 10nm to 50nm), and a nanomaterial solution with a mass concentration of 1% is prepared for surface coating of waste minerals to improve their surface activity and interface bonding properties.
[0074] Mixture proportion design: 55% waste mineral material, 30% coarse aggregate, 6% to 8% hot asphalt, 2% to 3% cement or lime powder, and the amount of nanomaterial added is 0.5% to 1.0% of the total mass.
[0075] Asphalt mixture production In the asphalt concrete mixing plant, raw materials are added in the following order: waste minerals, coarse aggregates, nanomaterial solution, auxiliary materials (cement or lime powder), and hot asphalt.
[0076] Start the automatic control system, set the stirring temperature to 165℃~175℃ and the stirring time to 90 seconds~120 seconds to ensure that the materials are mixed evenly.
[0077] Construction and laying The mixture is transported to the construction site and the road surface is paved using a paver with a paving thickness of 8cm to 12cm.
[0078] The initial compaction temperature is controlled at 95℃~110℃, and a steel wheel roller is used for compaction. The compaction times are 4 times, and the final compaction ensures that the road surface density meets the specification requirements.
[0079] Quality Control and Equipment Inspection During the production process, the stirring temperature and time are monitored in real time to ensure stable material properties.
[0080] Regularly check the operating status of screening machines, mixing equipment and transportation equipment to avoid fluctuations in material properties due to equipment problems.
[0081] Technical advantages and features Introduction of nanomaterials: Nano-silicon dioxide forms a highly active layer on the surface of waste minerals through surface coating, which significantly improves the interfacial bonding strength between minerals and asphalt, while enhancing the mechanical properties and durability of the mixture.
[0082] Optimization of material properties: After the introduction of nanomaterials, the internal structure of the mixture is denser, which effectively improves the compressive strength, fatigue resistance and resistance to water damage.
[0083] Multiple modification synergy: Nanomaterials work synergistically with cement / lime powder, not only strengthening the interaction between particles, but also further optimizing the stability of the mixture under high temperature and harsh environment.
[0084] Applicable scenarios for effect verification: Suitable for highways and heavy-load traffic sections, and projects with high requirements for mechanical properties and durability.
[0085] Expected performance improvement: Compared with the traditional process without the introduction of nanomaterials, the compressive strength is increased by about 15% to 20%, the fatigue life is extended by about 30% to 40%, and the water stability coefficient is increased to 0.92 to 0.96.
[0086] Economic and environmental benefits: Replacing machine-made sand can reduce material costs by about 20% to 30%, while achieving efficient resource utilization of waste minerals and reducing the pressure on mine waste storage.
[0087] This embodiment introduces nanomaterials based on the existing waste mineral utilization process, and comprehensively improves the performance of asphalt mixture through the dual effects of physical and chemical modification. It is suitable for engineering scenarios with higher requirements for road performance, and at the same time has significant economic and environmental value.
[0088] Proportional logic analysis Example and Comparative Example 1 Surface acidification and nanocatalyst loading are key processes to improve the interfacial bonding performance between waste mineral aggregates and asphalt. Failure to perform acidification or omitting catalyst loading will result in a significant decrease in bonding performance, making it difficult to meet the performance requirements of ordinary roads.
[0089] Example and Comparative Example 2 Highways require higher strength and durability, and failure to perform secondary calcination or omission of functional reinforcement materials will significantly weaken the fatigue performance and shear resistance of the mix.
[0090] Example and Comparative Example 3 Municipal road repair emphasizes economy. Failure to load a catalyst or insufficient calcination temperature will result in uneven quality of the mixture and failure to meet the durability requirements of municipal engineering. This shows that even in an economical design, key processes cannot be omitted.
[0091] Through multi-dimensional comparison between the embodiments and the comparative examples, the technical advantages and creativity of the present invention in the resource utilization of waste mineral materials are fully highlighted.
[0092] Experimental design In order to fully verify the effect of the present invention and its comparative advantages over the comparative examples, the following test experiments were designed. The experiments were carried out around the road performance, mechanical properties and economic efficiency of the mixture, focusing on compressive strength, fatigue resistance, shear strength and pavement durability, and analyzed in combination with application scenarios. The following experiments are divided into multiple test items, and the specific designs are as follows: Road performance test Purpose The road performance (such as compressive strength, shear strength and fatigue performance) of the asphalt mixture prepared by the present invention in different application scenarios (ordinary roads, expressways, municipal road repair) was verified, and the performance difference between the embodiment and the comparative example was compared.
[0093] Experimental methods Sample preparation: Each group prepared a standard Marshall specimen according to the recipe of Examples 1, 2, and 3, and the specimen dimensions were 101.6 mm in diameter and 63.5 mm in height.
[0094] The samples of comparative examples (1-1, 1-2, 1-3; 2-1, 2-2, 2-3; 3-1, 3-2) were prepared according to the corresponding formulas and parameters, which were consistent with the samples of the embodiments.
[0095] Each group of samples shall not be less than 6 pieces.
[0096] Test content and methods: Compressive strength test: The Marshall stability tester was used for testing with a loading rate of 50 mm / min. The maximum compressive load was recorded and the compressive strength was calculated.
[0097] Shear strength test: The shear strength of the mixture was measured using a direct shear test device at a shear rate of 1 mm / min.
[0098] Fatigue performance test: A dynamic fatigue testing machine was used to record the number of failures of the specimens under cyclic loading in a frequency of 10 Hz and constant strain mode.
[0099] Data analysis The numerical differences in compressive strength, shear strength and fatigue life between the examples and the comparative examples were compared, and the effects of surface treatment of waste ore, catalyst loading and high-temperature calcination on the performance were analyzed.
[0100] Expected results: The samples of the embodiments (especially embodiment 2) show higher compressive strength and shear strength, and the fatigue life is significantly better than that of the comparative samples.
[0101] Durability Test Purpose The durability of the mixture of the present invention was verified by simulating a long-term use environment, with a focus on analyzing the contribution of high-temperature calcination and surface treatment to durability.
[0102] Experimental methods Sample preparation: Prepare samples of Examples 1, 2, 3 and Comparative Examples (1-1, 2-1, 3-1), with no less than 4 pieces in each group.
[0103] Specimen dimensions: diameter 101.6 mm, height 63.5 mm.
[0104] Test content and methods: Freeze-thaw cycle test: The specimens were frozen at -18 °C for 24 hours and then transferred to a 20 °C water bath to thaw for 24 hours. The residual compressive strength was measured after 10 freeze-thaw cycles.
[0105] High temperature stability test: The rutting test of asphalt mixture was carried out in a high temperature environment of 60°C and the rutting depth was recorded.
[0106] Water stability test: Immersion Marshall test: the compressive strength of the sample is tested after it is immersed in water for 48 hours.
[0107] Data analysis The performance differences of the embodiments and comparative examples in freeze-thaw, high temperature and water stability tests were compared, and the effects of activation treatment of waste mineral materials and catalyst loading on durability were analyzed.
[0108] Expected results: Examples 1, 2, and 3 perform better in freeze-thaw loss, rutting depth, and water stability, especially Example 2 has more outstanding high temperature stability.
[0109] Economic analysis experiment Purpose The actual effect of reducing costs by replacing machine-made sand with waste mineral materials in the present invention is analyzed.
[0110] Experimental methods Cost calculation: Asphalt mixtures of Examples 1, 2 and 3 were prepared, and the comprehensive costs of waste mineral materials, functional enhancement materials, asphalt and processing energy consumption were calculated.
[0111] The comprehensive cost of the untreated waste ore and unloaded catalyst in the comparative examples (1-1, 2-1, 3-1) was calculated.
[0112] Compare the costs with the production costs of traditional machine-made sand asphalt mixtures.
[0113] Data Analysis: The cost proportions of each group are compared, and the economic advantages of the present invention in the resource utilization of waste minerals are analyzed.
[0114] Expected results: Examples 1 and 3 show higher economic efficiency, especially Example 3, the cost of which is 30% to 40% lower than that of the machine-made sand solution.
[0115] Application scenario adaptability experiment Purpose Combined with the actual requirements of repairing ordinary highways, expressways and municipal roads, the applicability of the present invention is verified.
[0116] Experimental methods Sample preparation: The samples of Example 1 and Comparative Examples (1-2, 1-3) were prepared for ordinary roads.
[0117] Samples of Example 2 and Comparative Examples (2-1, 2-2) were prepared for expressways.
[0118] The samples of Example 3 and Comparative Examples (3-1, 3-2) were prepared for municipal restoration.
[0119] Test content and methods: General highway applications: The compressive strength and fatigue performance were tested to determine the performance of Example 1 on a road surface with medium traffic volume.
[0120] Highway applications: The shear strength and rutting depth were tested to analyze the adaptability of Example 2 in heavy-load traffic.
[0121] Municipal Road Repair: The compressive strength and water stability were tested to analyze the adaptability of Example 3 in light-load traffic and low-cost requirements.
[0122] Data analysis The performance differences between the embodiments and the comparative examples in different application scenarios were compared, and the effect of process optimization on improving application adaptability was analyzed.
[0123] Expected results: The embodiments show better comprehensive adaptability, especially embodiment 2 can meet the high-intensity requirements of expressways, while embodiment 3 highlights the cost advantage.
[0124] Summarize The above experimental design fully combines the embodiments and comparative examples, and fully verifies the technical advantages of the present invention through tests of road performance, durability, economy and application scenario adaptability. Each experiment adopts standardized processes and comparative analysis, which can clearly highlight the creativity and practical application value of the present invention in the resource utilization of waste mineral materials, the improvement of mixture performance and cost control.
[0125] Experiment 1: Road performance test Experimental Description The experimental goal is to verify the contribution of key technologies (such as high temperature calcination, surface acidification treatment, nanocatalyst loading, etc.) in the process of the present invention to the improvement of the performance of the mixture by testing the compressive strength, shear strength and fatigue performance of the asphalt mixture of the embodiment and the comparative example. The experiment adopts the standard Marshall test method and the direct shear test method, and combines the dynamic fatigue performance test to comprehensively evaluate the road performance of each mixture.
[0126] Experimental procedures Sample preparation: Example samples: Samples were prepared according to the process formulas and parameters of Examples 1, 2, and 3, with no less than 6 samples in each group.
[0127] Comparative example samples: Samples were prepared according to the formulations and parameters of the comparative examples (1-1, 1-2, 1-3; 2-1, 2-2, 2-3; 3-1, 3-2), and the number and size were consistent with those of the example samples.
[0128] Specimen size: diameter 101.6mm, height 63.5mm, meeting the Marshall test standard.
[0129] Compressive strength test: A Marshall stability tester was used to load the specimen at the center at a loading rate of 50 mm / min, and the maximum load (kN) at failure was recorded.
[0130] Calculation formula for compressive strength (MPa): Where F is the maximum load and r is the specimen radius.
[0131] Shear strength test: Use a direct shear apparatus to test the shear strength, the shear rate is 1mm / min, record the shear force (kN) at failure, and calculate the shear strength (MPa) formula: Where F is the shear force and A is the shear surface area.
[0132] Fatigue performance test: A dynamic fatigue testing machine was used with the loading frequency set to 10 Hz and constant strain mode. Cyclic loads were applied and the number of loading times before the specimen was damaged (Nf) was recorded.
[0133] Data recording and analysis: The compressive strength, shear strength and fatigue life of each group of specimens are recorded separately and summarized into tabular data.
[0134] Experimental data The following is the test data of Experiment 1 (Table name: Road Performance Test Results). Group Compressive strength(MPa) Shear strength(MPa) Fatigue life (number of cycles) Example 1 5.2 1.15 18000 Comparative Example 1-1 4.3 0.98 10500 Comparative Example 1-2 4.7 1.02 12500 Comparative Examples 1-3 4.5 1.00 11000 Example 2 6.8 1.40 26000 Comparative Example 2-1 5.5 1.20 18500 Comparative Example 2-2 6.0 1.25 21000 Comparative Examples 2-3 5.7 1.22 19000 Example 3 4.8 1.05 14000 Comparative Example 3-1 4.1 0.92 9000 Comparative Example 3-2 4.3 0.95 9500
[0135] Summary and mechanism analysis based on Experiment 1 This experiment verified the improvement effect of the key processes of the present invention (such as high temperature calcination, surface acidification treatment, nano catalyst loading, etc.) on the performance of the mixture by testing the road performance of the examples and the comparative examples. The samples of the examples showed significant advantages in compressive strength, shear strength and fatigue life, especially the combination of high temperature calcination and nano cerium oxide loading in Example 2, which increased the compressive strength and fatigue life by about 24% and 40% respectively, fully meeting the high strength and high durability requirements of highways.
[0136] Compared with comparative example 1-1 (without acid treatment), the compressive strength and fatigue life of Example 1 are significantly improved. This is mainly due to the acidic active film layer formed on the surface of the mineral material by the acid treatment, which enhances the interfacial bonding force between the mineral material and the asphalt. At the same time, the loading of the nanocatalyst in the example further enhances the surface activity and chemical bonding ability of the mineral material. The samples of comparative example 1-2 have a slight decrease in performance due to the lack of catalyst treatment, especially the fatigue life is only about 70% of that of the example.
[0137] The test results of Example 3 demonstrate the applicability of the economical mixture in municipal road repair. Although slightly inferior to Example 1 in terms of compressive strength and fatigue life, it can still meet the basic performance requirements of municipal engineering and significantly reduce production costs by moderately simplifying the process and reducing the treatment intensity. However, both Comparative Examples 3-1 (no catalyst loading) and 3-2 (insufficient calcination temperature) showed obvious performance degradation, especially in the fatigue life test, the number of loading times was reduced by about 35% to 40%, reflecting the key role of catalyst loading and high-temperature calcination in the activation treatment of mineral materials.
[0138] Combined with the mechanism analysis, high-temperature calcination enhances the chemical reactivity of the mineral material by removing adsorbents on the surface of the mineral material and exposing active sites; the synergistic effect of acidification treatment and nanocatalysts further enhances the binding force between the mineral material and asphalt molecules, thereby significantly improving the mechanical properties and fatigue life of the mixture. This experiment fully verifies the technical advantages of the present invention in the resource utilization of waste mineral materials, especially in different scenarios of ordinary roads, highways and municipal roads, which all reflect excellent road performance and economic benefits.
[0139] Experiment 2: Durability Test Experimental Description The experimental goal is to verify the durability of the asphalt mixture prepared by the present invention, especially the resistance to freeze-thaw damage, high temperature stability and water stability, by simulating a long-term use environment (such as freeze-thaw cycles, high temperature conditions and water immersion). By comparing the embodiments with the comparative examples, the contribution of high temperature calcination, surface acidification treatment and nanocatalyst loading to durability in the process of the present invention is further revealed.
[0140] Experimental procedures Sample preparation: According to the process parameters of Examples 1, 2, 3 and Comparative Examples (1-1, 1-2, 1-3; 2-1, 2-2, 2-3; 3-1, 3-2), Marshall specimens with a diameter of 101.6 mm and a height of 63.5 mm were prepared, with no less than 6 specimens in each group.
[0141] Freeze-thaw cycle test: The samples were frozen at -18°C for 24 hours and then transferred to a 20°C water bath to thaw for 24 hours.
[0142] After completing 10 freeze-thaw cycles, the Marshall stability test was performed to calculate the residual compressive strength ratio (TSR) of the specimens before and after the freeze-thaw cycle. The formula is as follows: High temperature stability test: The samples were subjected to a rutting test in a 60°C constant temperature box, a loading device was used to simulate the vehicle load, and the rutting depth (mm) was recorded.
[0143] Water stability test: According to the immersion Marshall test method, the sample is immersed in a 60°C water bath for 48 hours, and then its compressive strength is tested and the water stability coefficient (immersion compressive strength / initial compressive strength) is calculated.
[0144] Experimental data The following is the test data of Experiment 2 (Table name: Durability Test Results). Group Freeze-thaw residual compressive strength ratio (%) Rutting depth (mm) Water stability coefficient Example 1 88.4 2.5 0.93 Comparative Example 1-1 71.2 4.1 0.80 Comparative Example 1-2 78.5 3.7 0.85 Comparative Examples 1-3 74.3 3.9 0.82 Example 2 92.6 2.1 0.96 Comparative Example 2-1 83.7 3.2 0.88 Comparative Example 2-2 86.1 2.8 0.90 Comparative Examples 2-3 84.5 3.0 0.89 Example 3 82.3 3.5 0.88 Comparative Example 3-1 67.4 4.6 0.75 Comparative Example 3-2 70.8 4.3 0.78
[0145] Summary and mechanism analysis based on Experiment 2 The durability test results show that the samples of the embodiment are significantly better than the samples of the comparative example in terms of freeze-thaw cycles, rutting depth and water stability coefficient. Example 1 shows good freeze-thaw compressive strength in ordinary highway applications, and its freeze-thaw residual compressive strength ratio is as high as 88.4%, which is significantly higher than 71.2% of comparative example 1-1. This is due to the improvement of the surface chemical properties of the mineral material by acidification treatment and nanocatalyst loading, which forms a more stable interface between the mineral material and the asphalt, thereby reducing the damage caused by water intrusion during the freeze-thaw cycle. In comparison, comparative example 1-1 was not acidified, and there was still a loose impurity layer on the surface of the mineral material, which was difficult to effectively prevent water intrusion, resulting in a decrease in freeze-thaw performance.
[0146] The high temperature stability test of Example 2 is particularly outstanding, with a rutting depth of only 2.1 mm, which is much lower than the 3.2 mm of Comparative Example 2-1. This difference is mainly due to the fact that Example 2 uses the synergistic treatment of high temperature calcination and nano-cerium oxide, which significantly improves the high temperature deformation resistance and interface bonding strength of the waste mineral material. Mechanistically, high temperature calcination exposes the active sites on the surface of the mineral material, and nano-cerium oxide further enhances the physical and chemical bonding strength between the mineral material and the asphalt molecules, thereby improving the anti-rutting ability of the mixture under high temperature conditions. However, since the secondary calcination step is omitted in Comparative Example 2-1, the mineral material and the asphalt are not fully combined, resulting in an increase in the rutting depth.
[0147] In the municipal road repair scenario, the water stability coefficient of Example 3 reaches 0.88, which meets the basic needs of light-load traffic. However, since the comparative example 3-1 is not loaded with a catalyst, the water stability coefficient of the sample is only 0.75, showing obvious performance deficiencies. This shows that even in economical designs, the role of nanocatalysts cannot be ignored. Nanocatalysts not only improve the surface chemical properties of the mineral material, but also form a stable chemical film layer at the interface, effectively preventing the penetration and diffusion of water. The mineral material in the comparative sample that is not loaded with a catalyst is easily degraded due to water infiltration.
[0148] In summary, this experiment fully verifies the contribution of high temperature calcination, acidification treatment and nanocatalyst loading to durability improvement in the present invention. In terms of mechanism, the waste mineral material not only removes the surface impurity layer through multiple treatment processes, but also significantly enhances the chemical bonding force between the mineral material and the asphalt interface, thereby showing excellent durability under harsh conditions such as freeze-thaw, high temperature and water immersion. This advantage makes the mixture of the present invention have good applicability and economy in application scenarios such as ordinary roads, highways and municipal road repairs.
[0149] Experiment 3: Application scenario adaptability test Experimental Description The experimental goal is to verify the performance adaptability of the present invention in different scenarios for the actual application needs of ordinary roads, highways and municipal road repair. The experiment compares the performance differences between the embodiment and the corresponding proportion through comprehensive tests of compressive strength, shear strength, rutting depth and water stability coefficient to verify the applicability of the present invention in actual engineering applications.
[0150] Experimental procedures Sample preparation Samples of the embodiments: Samples were prepared according to the formulations and parameters of Examples 1, 2 and 3, with each group of samples being no less than 6.
[0151] Comparative example samples: Samples were prepared according to the formulas and parameters of comparative examples 1-1, 1-2, 1-3; 2-1, 2-2, 2-3; 3-1, 3-2, and the number and size of the samples were consistent with those of the embodiments.
[0152] Specimen dimensions: diameter 101.6 mm, height 63.5 mm.
[0153] Ordinary road suitability test Compressive strength test: Use Marshall stability tester to perform compressive strength test, with a loading rate of 50mm / min, record the maximum load at failure, and calculate the compressive strength.
[0154] Shear strength test: A direct shear apparatus was used to test the shear strength. The shear rate was 1 mm / min. The shear failure load was recorded and the shear strength was calculated.
[0155] Highway suitability test Rutting depth test: A simulated rutting test was conducted in a 60°C high temperature rutting instrument, and the rutting depth (mm) formed under the vehicle load was recorded.
[0156] Fatigue performance test: A dynamic fatigue testing machine was used with a loading frequency of 10 Hz to record the number of cyclic loading times (Nf) before the specimen was damaged.
[0157] Municipal road repair suitability test Water stability test: According to the immersion Marshall test method, the compressive strength of the sample was tested after immersion in a 60℃ water bath for 48 hours, and the water stability coefficient was calculated.
[0158] Compressive strength test: consistent with ordinary highway test method.
[0159] Experimental data The following is the test data of Experiment 3 (table name: Application scenario adaptability test results).
[0160] Summary and mechanism analysis based on Experiment 3 The experimental results show that the mixture of the present invention exhibits excellent adaptability in three typical application scenarios of ordinary highway, expressway and municipal road repair, especially in terms of compressive strength, shear strength and rutting depth, which are significantly better than the corresponding proportions. This performance advantage fully reflects the interface bonding enhancement effect achieved by the present invention through surface treatment of waste minerals and loading of nanocatalysts.
[0161] In ordinary road scenarios, the compressive strength and shear strength of Example 1 reach 5.3MPa and 1.16MPa, respectively, which are about 20% and 22% higher than those of Comparative Example 1-1. This is because the present invention uses high-temperature calcination and acidification treatment to remove impurities and organic matter adsorbed on the surface of the mineral material, making the surface of the mineral material cleaner. At the same time, the acidic active film layer enhances the interfacial bonding force with asphalt. However, since Comparative Example 1-1 was not subjected to acidification treatment, impurities remained on the surface of the mineral material, making it difficult to form a stable interface bonding, resulting in poor mechanical properties.
[0162] In the highway scenario, the rutting depth of Example 2 is only 2.3 mm, and the fatigue life is 25,000 times, which is much better than 3.1 mm and 18,000 times of Comparative Example 2-1. This shows that the synergistic effect of high-temperature calcination and nano-cerium oxide loading significantly improves the high-temperature stability and fatigue resistance of the mineral material. Mechanistically, high-temperature calcination exposes the active sites on the surface of the mineral material, and the reinforced film formed by nano-cerium oxide at the interface further improves the deformation resistance of the mixture. Comparative Example 2-1 did not undergo secondary calcination, and the active sites on the surface of the mineral material were insufficient, and the interface bonding force was weak, so it showed obvious performance degradation under high temperature conditions.
[0163] In the municipal road repair scenario, the water stability coefficient of Example 3 reached 0.89, which is significantly better than 0.77 of Comparative Example 3-1. The introduction of the nanocatalyst formed a chemically stable protective layer on the surface of the mineral material, effectively preventing the intrusion of water. However, since Comparative Example 3-1 was not loaded with a catalyst, the surface of the mineral material lacked a chemical protective layer, and its performance rapidly decreased under water immersion. This result fully proves that even in an economical design, catalyst loading still plays an important role in improving water resistance and interface bonding ability.
[0164] In summary, the present invention realizes the resource utilization and high-performance modification of waste minerals through the three core technologies of high-temperature calcination, acidification treatment and nanocatalyst loading. It is suitable for various engineering scenarios such as ordinary highway, expressway and municipal road repair. These technical optimizations not only improve the mechanical properties and durability of the mixture, but also significantly enhance its adaptability to complex working conditions. It has broad engineering application prospects and economic value.
[0165] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A process for producing asphalt concrete using waste mineral materials instead of machine-made sand, characterized in that: The following steps are involved: Screening the waste minerals to obtain fine aggregates with a particle size of 0.075 mm to 2.36 mm; The screened waste ore is calcined at high temperature; Carry out surface acidification treatment on waste ore after high-temperature calcination; Loading nanocatalysts on waste mineral materials that have undergone surface acidification treatment; Introducing surfactants on the surface of waste mineral materials; Mixing waste minerals, coarse aggregates, asphalt and functional enhancement materials in proportion to prepare asphalt mixture, wherein the mass percentage of waste minerals is 50% to 70%, the mass percentage of coarse aggregates is 20% to 30%, the mass percentage of asphalt is 5% to 8%, and the mass percentage of functional enhancement materials is 0.5% to 1.5%; The prepared asphalt mixture is used for road construction.
2. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1 is characterized in that: The high-temperature calcination temperature of the waste ore is 600° C. to 800° C., the calcination time is 1.5 hours to 2 hours, and the high-temperature calcination equipment is a rotary kiln.
3. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1 is characterized in that: The surface acidification treatment comprises the following steps: Prepare a mixed acid solution, wherein the mixed acid solution is a mixture of 5% to 10% phosphoric acid and dilute hydrochloric acid in a ratio of 1:1, and adjust the pH value to 4.5 to 6; Soaking the calcined waste ore in the mixed acid solution for 30 to 60 minutes; The soaked waste minerals are rinsed with deionized water and dried.
4. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1 is characterized in that: The nano catalyst is nano titanium dioxide or nano cerium oxide with a particle size of 10nm to 50nm, and the mass concentration of the nano catalyst solution is 0.5% to 1.5%.
5. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1 is characterized in that: The nanocatalyst loading comprises the following steps: Placing the waste mineral material in a vacuum coating device and uniformly spraying the nano catalyst solution; Dry the sprayed waste mineral material at a temperature of 100°C to 120°C for 1 to 2 hours; The dried waste ore is subjected to secondary calcination, the calcination temperature is 400° C. to 600° C., and the calcination time is 0.5 hour to 1 hour.
6. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1 is characterized in that: The surfactant is nonylphenol polyoxyethylene ether or sulfonate, and the mass concentration of the surfactant solution is 0.1% to 0.5%.
7. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1 is characterized in that: The surfactant is introduced onto the surface of the waste mineral material by spraying, and is dried after being stirred evenly at room temperature.
8. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1 is characterized in that: The functional enhancement material is cement, lime powder or modified epoxy resin, wherein the addition amount of cement or lime powder is 2% to 3%, and the addition amount of modified epoxy resin is 0.5% to 1%.
9. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1 is characterized in that: The stirring temperature of the asphalt mixture is 160° C. to 180° C., and the stirring time is 90 seconds to 120 seconds.
10. The asphalt concrete production process using waste mineral materials instead of machine-made sand according to claim 1, characterized in that: When the asphalt mixture is used for road construction, the paving thickness is 5 cm to 15 cm, the initial compaction temperature is 90° C. to 110° C., and a steel wheel roller is used for compaction 3 to 5 times.
Citation Information
Patent Citations
Method for preparing asphalt pavement material by adopting waste concrete
CN101624274A
Regenerated semi-flexible pavement material and preparation method thereof
CN103450692A
Iron tailing sand asphalt mixture
CN103833266A
High-viscosity high-elasticity asphalt based on surface modification of rubber particles, and high-viscosity high-elasticity SMA (stone mastic asphalt) mixture based on surface modification of rubber particles and preparing method thereof
CN104725883A
High-strength recycled concrete and preparation method thereof
CN109456002A